DAGmaps: Space Filling Visualization of Directed Acyclic Graphs - Tsiaras, Vassilis; Triantafilou, Sofia; Tollis, Ioannis (Journal of Graph Algorithms and Applications, 2009)
Gene Ontology information related to the biological role of genes isorganized in a hierarchical manner that can be represented by adirected acyclic graph (DAG). Space filling visualizations, such as the treemaps,have the capacity to display thousands of items legibly inlimited space via a two-dimensional rectangular map. Treemapshave been used to visualize the Gene Ontology by first transformingthe DAG into a tree. However this transformation has severalundesirable effects such as producing trees with a large number ofnodes and scattering the rectangles associated with the duplicatesof a node around the display rectangle. In this paper we introduce the problemof visualizing a DAG with space filling techniques withoutconverting it to a tree first,we present two special cases of the problem,and we discuss complexity issues. <!---->